Outcome of Multilevel Anterior Cervical Discectomy and Fusion without Plating - Omar Taher , Avin; Khaleel , Imad; Rawandozy , Anjam; Abdulla , Firas (Diyala Journal of Medicine, 2023)
Background: Multilevel anterior cervical discectomy and fusion (ACDF) procedure had traditionally been associated with plating, however, the increase in cost and complications associated with plating led us to investigate results of multilevel ACDF with polyether ether ketone (PEEK) cages without plating and study complication and fusion rates. Objective: To evaluate the clinical and radiological outcome of patients underwent multilevel Anterior Cervical Discectomy and Fusion (ACDF) using polyether ether ketone (PEEK) cage with no plating. Patients and Methods: Sixty patients underwent multilevel Anterior Cervical Discectomy and Fusion (ACDF), Surgical approach, using Polyether Ether Ketone (PEEK) cages with synthetic bone graft material with no plating. Their mean age was 48 year. All patients were evaluated clinically and radiologically for a mean time of one year. Assessment done comparing early and late post-operative cervical spinal x-rays for cage subsidence and migration. Improvement in axial neck and radicular pain were assessed using the Visual Analogue Score (VAS). Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS), A p value of ≤ 0.05 was considered statistically significant. Results: Sixty patients underwent Anterior Cervical Discectomy with Fusion (ACDF) through Cloward approach. F:M ratio was 1:1. Two levels were operated in 75% of patients, while in 25% three levels were operated. The majority 85% underwent operation at C5-6 level, least operated levels were C3-C4 and C6-C7 36.7% and 66.7% underwent operation at C4-C5 level. None underwent operation at C2-C3 level. There was significant improvement in axial neck pain with VAS decreasing from 6 to 2, radicular pain improved from 7 to 2. Only one patient (1.7%) showed radiological subsidence of 3 mm after 6 months of operation with no further progression, cage slippage was observed in 2 patients (3.3%) by 1 mm in both cases but no radiological progression. All patients (100%) showed good fusion. Conclusion: Multilevel ACDF with PEEK cages without plating showed to be safe option and provided good fusion rates and clinical outcome in our patients.